2018 IEEE Conference on Decision and Control (CDC) 2018
DOI: 10.1109/cdc.2018.8619225
|View full text |Cite
|
Sign up to set email alerts
|

A Feedback-Based Regularized Primal-Dual Gradient Method for Time-Varying Nonconvex Optimization

Abstract: This paper considers a nonconvex optimization problem that evolves over time, and addresses the synthesis and analysis of regularized primal-dual gradient methods to track a Karush-Kuhn-Tucker (KKT) trajectory. The proposed regularized primal-dual gradient methods are implemented in a running fashion, in the sense that the underlying optimization problem changes during the iterations of the algorithms. For a problem with twice continuously differentiable cost and constraints, and under a generalization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Examples of works include real-time algorithms for voltage control, OPF, as well as DER management for aggregators (see, for example, [60]- [65] and pertinent references therein). For some applications, such as the demand response and the OPF, online algorithms have been designed to leverage measurements of constraints (e.g., voltages violations) in the algorithmic updates [18], [61], [66] to relax the sensing requirements. Real-time measurements were used in a state estimation framework in [67].…”
Section: Cyber-physical Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of works include real-time algorithms for voltage control, OPF, as well as DER management for aggregators (see, for example, [60]- [65] and pertinent references therein). For some applications, such as the demand response and the OPF, online algorithms have been designed to leverage measurements of constraints (e.g., voltages violations) in the algorithmic updates [18], [61], [66] to relax the sensing requirements. Real-time measurements were used in a state estimation framework in [67].…”
Section: Cyber-physical Systemsmentioning
confidence: 99%
“…The algorithm produces decisions on setpoints for the active and reactive power outputs xi(t k ) of the DERs, which are commanded to the devices. Finally, "feedback" can come in the form of measurements of the actual power outputs xi(t k ) [60], as well as other electrical quantities [61], [66].…”
Section: T W O a P P L I C A T I O N S : D E E P D I V E A Example In Power Gridsmentioning
confidence: 99%
“…Second, we do not make restrictive assumptions on RIP properties, incoherence, identical covariance matrices, independence of all outlier supports, or initialisation. Broadly speaking, such analyses of time-varying non-convex optimisation (Liu et al 2018;Tang et al 2018;Fattahi et al 2019;Massicot and Marecek 2019), seems to be an important direction for further research.…”
Section: Discussionmentioning
confidence: 99%
“…In recent works we showed that "worst-case" sensitivity bounds provide privacy guarantees when releasing power flow data [16] and for data disaggregation [23]. In the context of real-time optimization where sensitivity is often assumed to be known and bounded [24], this work can be used to provide exactly these bounds (or rule them out).…”
Section: A Summarymentioning
confidence: 99%